2019
DOI: 10.1590/1413-81232018248.24102017
|View full text |Cite
|
Sign up to set email alerts
|

Preference for death at home and associated factors among older people in the city of Belo Horizonte, Brazil

Abstract: We examined people’s preferences for place of death and identified factors associated with a home death preference. We asked a representative sample (N = 400) of older people (≥ 60 years) residents in the city of Belo Horizonte, about their preferences for place of death in a situation of serious illness with less than a year to live. Data were analyzed using binomial regression to identify associated factors. 52.2% indicate home as the preferred place of death. Five variables were associated with preference f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
1
6
0
5
Order By: Relevance
“…Embora achados na literatura nacional não demonstrem claramente a importância do estado civil na QV de pacientes em CP, pacientes com câncer e que vivem em união estável ou casados têm mais chances de sobrevivência do que aqueles que vivem só 26,36,37 . No presente estudo, os pacientes divorciados obtiveram os piores escores médios do POS (17,25), em comparação aos casados (16,6) e com união estável (15), o que fornece indícios sobre a provável importância do suporte social prestado por pessoas próximas ao paciente no enfrentamento da doença.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Embora achados na literatura nacional não demonstrem claramente a importância do estado civil na QV de pacientes em CP, pacientes com câncer e que vivem em união estável ou casados têm mais chances de sobrevivência do que aqueles que vivem só 26,36,37 . No presente estudo, os pacientes divorciados obtiveram os piores escores médios do POS (17,25), em comparação aos casados (16,6) e com união estável (15), o que fornece indícios sobre a provável importância do suporte social prestado por pessoas próximas ao paciente no enfrentamento da doença.…”
Section: Discussionunclassified
“…A promoção de CP em ambiente domiciliar permite aos pacientes a possibilidade de permanecer em seu contexto familiar e social 14,15 , com atenção multiprofissional, especializada e disposta a oferecer suporte e orientação aos familiares e/ou cuidadores, evitando internações recorrentes e muitas vezes desnecessárias 16,17 . Entretanto, os cuidados domiciliares ainda são uma prática pouco frequente em muitos locais, haja vista a sua forte predominância nos espaços hospitalares 17 .…”
Section: Introductionunclassified
“…It is possible that the participants who chose the option "home of relative/friend" fear that they would have less decision-making autonomy in this setting and therefore want more information than those who chose "own home", where their preferences are more likely to be respected. However, the evidence on place of death remains unclear, particularly among the older population, and less evidence exists regarding least preferred place of death 2,42,30 . Further research is therefore needed to explore the influence of these factors on preferences.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies showed that the majority of older cancer patients preferred not to be informed about expected survival 14 , did not want complete information on their disease 24 , preferred to receive more information about the diagnosis than the prognosis 14,25,26 , and wanted to receive less information than younger patients 14,24,27 . A population-based study carried out in Europe reported that people aged under 70 were more likely to want to know if they had limited time left 3 , while a study conducted in Belgium showed that younger participants (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) and 45-54 years) were more likely to want to be fully informed about their disease 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation